Disaster control and planning in a universal library (2011)
University library is a type of academic library. They have long been repositories of knowledge and safe house for undisturbed study. While they are considered safe and quite places to conduct scholarly research, they are susceptible to hazards like any other organisation. Treasures in libraries may be destroyed by unforeseen hazards which may be either man-made or natural disasters such as acts of war and terrorism, fire and smoke, water damage from leaks or floods, earthquakes, volcanic eruptions, tornadoes, ice and snow, thunderstorms and power outages, etc. Disasters are unpredictable in their nature, occurrence and severity. Disaster planning is a basic security for library staff and collections. While library disasters cannot be prevented, their impact on library services might be minimized with a formal written plan which will enhance prompt response to the emergency. This study established that while disaster is an inevitable element in the library however, its impact on library holdings might be minimised through advance planning and preparedness. These are the keys to preventing or at least reducing the impacts of these potential hazards. As a result of the valuable resources in the libraries, it is essential to minimize disaster by planning against its occurrence. The study examines the types and causes of disaster in academic libraries, and presents guidelines for disaster planning. It was recommended that university libraries should renew their commitment to protecting the valuable collections in their custody through a functional disaster plan.